Surface Coatings—1
XII, 274 p.
Keywords: The field of surface coatings is now so extensive, and is developing so rapidly, that no individual person could be expected to master it in its entirety. Hence, the days have gone when a lone author could compile a comprehensive treatise on the topic without overlooking many of the most significant developments. Yet the very growth and diversity of surface coatings make it essential that workers in the field should have access to up-to-date and authoritative reviews. It is to satisfy this need that we have assembled our team of authors, each of whom is an expert in his or her branch of the subject, and is well able to as'sess w:hat is most significant and exciting within that branch. They h,ave b~en encouraged to develop their themes in what they have felt to be the most appropriate way, with minimal editorial interference from us. We believe that the results of their labours will be of benefit to those engaged not only in basic research, but also to those working ip product development and in testing and evaluation of coatings.